ARBUSCULAR MYCORRHIZAL FUNGI IN BISBUL TREES (Diospyros blancoi) IN BOGOR - Ningsih, Dwi Retno; Kramadibrata, Kartini; Gunawan, Agustin Wydia (BIOTROPIA, 2013)
Bisbul (Diospyros blancoi) isa kind of edible fruit and could be beneficial as inhibitor forskin ageing process.Majority of root plants have symbiotic associations with arbuscular mycorrhizal fungi (AMF); however, AMFinbisbul has never been reported. The objective of this study was to observe AMF colonies and to identify AMF spores in bisbul tree rhizospheres and in pot-cultured Pueraria javanica. Roots and soil samples from bisbul rhizospheres were collected from three locations in Bogor area. Roots were stained using trypan blue 0.05%.  Soil samples were air dried, then part of them were used for spore isolation and the rest were used for pot cultures. Spores wereisolated by wet sieving and decanting method and then continued with centrifugation. The results showed that the structures of AMF colonies in bisbul roots were arbuscules, vesicles, coiled hyphae, and  internal hyphae. Isolated AMF spores were identified as Acaulospora longula, A. scrobiculata, A. tuberculata, Claroideoglomus geosporum,Funneliformis etunicatum,Gigaspora candida, G. ramisporophora, Glomus albidum, G. glomerulatum, and Scutellospora calospora. This is the first report of mycorrhizal infection in the root of bisbul and AMF association with bisbul root. Keywords:  Acaulospora, Claroideoglomus, Funneliformis, Gigaspora, Glomus,  Indonesia, Scutellospora